Local civil society regimes: liberal, corporatist and social democratic civil society regimes in Swedish metropolitan cities. (31st March 2018) - Arvidson, Malin; Johansson, Håkan; Johansson, Staffan; Nordfeldt, Marie
Abstract : Academic debates on the role and position of civil society organisations (CSOs) in welfare states largely refer to policies and practices outlined at the national level. They therefore fail to recognise variations within nations. Based on a comparative case study of three Swedish metropolitan cities, this article illustrates the importance of local, contextualised analyses. Through the concept of local civil society regimes, the study identifies three regime types, namely liberal, corporatist and social democratic. The key distinguishing factor between them relates to their different ideological positions regarding the role of CSOs in the marketisation and privatisation of public social welfare represented at the local level. The article argues for the need for further analysis to explore the implications of decentralisation from the perspective of local CSOs and their constituencies.